2022
DOI: 10.1097/pcc.0000000000003150
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Positive Post-Traumatic Stress Disorder Screening and Associated Outcomes in Children Surviving Acute Respiratory Failure: A Secondary Analysis of the Randomized Evaluation of Sedation Titration for Respiratory Failure Clinical Trial

Abstract: To identify risk factors and outcomes associated with a positive post-traumatic stress disorder (PTSD) screen following pediatric acute respiratory failure treated with invasive mechanical ventilation. DESIGN:Nonprespecified secondary analysis of a randomized clinical trial.SETTING: Thirty-one U.S. PICUs. PATIENTS:Children in the Randomized Evaluation of Sedation Titration for Respiratory Failure (RESTORE) trial (NCT00814099, ClinicalTrials. gov) over 8 years old who completed PTSD screening 6 months after dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Analysis of a big randomized clinical trial in the pediatric population showed that screening positively for PTSD after a pediatric intensive care unit (PICU) stay was associated with lower income in the family's residential zip code, renal dysfunction and significant pain during hospitalization. Children screened positively for PTSD experienced a decrease in cognitive function and health-related quality of life [5]. Significantly, ICU stay is a factor that separately declines health-related quality of life [6,7,8].…”
Section: Epidemiologymentioning
confidence: 99%
“…Analysis of a big randomized clinical trial in the pediatric population showed that screening positively for PTSD after a pediatric intensive care unit (PICU) stay was associated with lower income in the family's residential zip code, renal dysfunction and significant pain during hospitalization. Children screened positively for PTSD experienced a decrease in cognitive function and health-related quality of life [5]. Significantly, ICU stay is a factor that separately declines health-related quality of life [6,7,8].…”
Section: Epidemiologymentioning
confidence: 99%
“…P ediatric critical illness is associated with pain, anxiety, and delirium that may contribute to lower health-related quality of life (HRQL) and poor mental health outcomes after discharge (1)(2)(3). However, family presence during pediatric hospitalization may mitigate some of these adverse effects.…”
mentioning
confidence: 99%